Perancangan Baby Box Multifungsi Pada Baby Spa Centre Di Surabaya - Michelle Claudia Kohar (Intra, 2017)
The high economic demands in Indonesia causing so many parents spend most of their time earning money for living, so they do not have enough time to take care of their babies. This is where the role of a baby spa center is needed to help the parent's part to caring and to look after their babies. However, parents have their important considerations in terms of choosing a baby spa center that is safe and feasible for their babies. In this case, a multifunctional furniture designed not only to supports the baby's needs but also facilitates and supporting the therapist's work.This furniture design must have the safety and comfort standards of babies and therapists as the users. Not only safe and comfortable, but furniture also have an innovative design and environmentally friendly with the right material selection and finishing.